Scavenger and antioxidant properties of prenylflavones isolated from Artocarpus heterophyllus - Ko, F.N.; Cheng, Z.J.; Lin, C.N.; Teng, C.M.
The antioxidant properties of prenylflavones, isolated from Artocarpus heterophyllus Lam., was evaluated in this study. Among them, artocarpine, artocarpetin, artocarpetin A, and cycloheterophyllin diacetate and peracetate had no effect on iron-induced lipid peroxidation in rat brain homogenate. They also did not scavenge the stable free radical 1,1-diphenyl-2-picrylhydrazyl. In contrast, cycloheterophyllin and artonins A and B inhibited iron-induced lipid peroxidation in rat brain homogenate and scavenged 1,1-diphenyl-2-picrylhydrazyl. They also scavenged peroxyl radicals and hydroxyl radicals that were generated by 2,29-azobis(2-amidinopropane)dihydrochloride nd the Fe31- ascorbate-EDTA-H2O2 system, respectively. However, they did not inhibit xanthine oxidase activity or scavenge superoxide anion, hydrogen peroxide, carbon radical, or peroxyl radicals derived from 2,29-azobis(2,4-dimethylvaleronitrile)in hexane. Moreover, cycloheterophyllin and artonins A and B inhibited copper-catalyzed oxidation of human low-density lipoprotein, as measured by fluorescence intensity, thiobarbituric acid-reactive substance and conjugateddiene formations and electrophoretic mobility. It is concluded that cycloheterophyllin and artonins A and B serve as powerful antioxidants against lipid peroxidation when biomembranes are exposed to oxygen radicals.
Keywords: ANTIOXIDANT; LIPID PEROXIDATION; LOW-DENSITY LIPOPROTEIN; PRENYLFLAVONE; ARTOCARPUS HETEROPHYLLUS; FREE RADICAL